2023
DOI: 10.1021/acs.jafc.3c01010
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of l-Theanine on Cyclophosphamide-Induced Testicular Toxicity in Mice

Abstract: L-Theanine is the most abundant free amino acid present in tea. Several tea components have been studied for their impact on male fertility, but little is known about the effects of L-theanine. Cyclophosphamide (CP) is an antineoplastic and immunosuppressive agent that reduces fertility in males. In the present study, we evaluated the effect of L-theanine on CP-induced testicular toxicity in male mice. A single dosage of 50 mg/kg saline or CP was administered intraperitoneally over the course of 5 days. Mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…37–40 Additionally, chemotherapy-treated mice administered with LTA showed an increased body weight, testicular organ index, and serum testosterone levels. 44 This indicates that LTA may enhance testicular injury recovery and modulate reproductive function. However, the protective effects of LTA and DHM against reproductive function impairment induced by heat stress remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…37–40 Additionally, chemotherapy-treated mice administered with LTA showed an increased body weight, testicular organ index, and serum testosterone levels. 44 This indicates that LTA may enhance testicular injury recovery and modulate reproductive function. However, the protective effects of LTA and DHM against reproductive function impairment induced by heat stress remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…5 days of pretreatment with the amino acid resulted in reduction of testicular damage concerning spermatogonial cells, epithelial cells, seminiferous tubules and basement membrane. [34]…”
Section: Anti-cancer Propertiesmentioning
confidence: 99%
“…Stankiewicz et al, reported that oxidative stress and elevated reactive oxygen species (ROS) could play an important role in cyclophosphamide-induced kidney damage 3 . Furthermore, prior studies demonstrated that cyclophosphamide could inhibit the activities of antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT) 4,5 . Other theories related to nephrotoxicity due to cyclophosphamide were imbalance of the oxidants-antioxidants system, increase of the inflammatory cytokines, and apoptosis 6 , although there is no consensus that, to prevent the toxicity due to cyclophosphamide, a potent antioxidant agent could be useful.…”
Section: Introductionmentioning
confidence: 99%